All-printed humidity sensor based on gmethyl-red/methyl-red composite with high sensitivity. (August 2016) - Ali, Shawkat; Hassan, Arshad; Hassan, Gul; Bae, Jinho; Lee, Chong Hyun
Abstract: To monitor the most common constituted H2 O in the air for health and environment applications, we propose a highly sensitive humidity sensor consisted of silver inter-digital electrodes and graphene (G)/methyl-red (M-R) composite layer. Dimension of the proposed silver inter-digital electrodes is 200 μm finger width, 400 μm spacing, and 400 nm thickness, which is fabricated on a low cost transparent polyethyleneterephthalate (PET) substrate through commercialized Dimatix material inkjet printer (DMP-3000). To achieve a high sensitivity and wide sensing range, the composite thin film layer is deposited over the silver inter-digital electrodes through electrohydrodynamic (EHD), and its thickness is ∼300 nm. The sensor electrical resistance inversely varies from 11 MΩ to 0.4 MΩ against the relative humidity (RH) content from 5% to 95%. The proposed humidity sensor showed 96.36% resistive and 2869500% capacitive sensitivity against humidity. The response and recovery time of the proposed sensor is 0.251s and 0.35s, respectively.